NCC regulation by WNK signal cascade - Uchida, Shinichi; Mori, Takayasu; Susa, Koichiro; Sohara, Eisei (Frontiers in Physiology, 2023)
With-no-lysine (K)(WNK) kinases have been identified as the causal genes for pseudohypoaldosteronism type II (PHAII), a rare hereditary hypertension condition characterized by hyperkalemia, hyperchloremic metabolic acidosis, and thiazide-hypersensitivity. We thought that clarifying the link between WNK and NaCl cotransporter (NCC) would bring us new mechanism(s) of NCC regulation. For the first time, we were able to produce a knock-in mouse model of PHAII and anti-phosphorylated NCC antibodies against the putative NCC phosphorylation sites, and then discovered that constitutive activation of NCC and increased phosphorylation of NCC are the primary pathogenesis of the disease in vivo. We have since demonstrated that this regulatory mechanism is mediated by the kinases oxidative stress-response protein 1 (OSR1) and STE20/SPS1-related proline/alanine-rich kinase (SPAK) (WNK-OSR1/SPAK-NCC signaling cascade) and that the signaling is not only important in the pathological condition of PHAII but also plays a crucial physiological role in the regulation of NCC.